Assessment of Localization Performances in Wireless Sensor Networks - Jamalullah, Syed R; RajaLakshmi, V (International Journal of Computer Sciences and Engineering, 2025)
Wireless Sensor Networks (WSNs) has gained special deliberation among research groups with its assuming technology in wireless communication field. Wireless sensors are contiguously scattered and enthusiastic for recording and monitoring the environmental physical activity such as target tracking, defences, disaster relief and many more. The important function of sensor network is to collect and sends the data to its destination where the awareness of location (Viz. location of data) is a crucial challenge in (WSNs). This kind of information can be availed using localization techniques. For many wireless sensor networks applications, Localization has been regarded as one of the significant and aiding technology. It is also a way to govern the location of sensor nodes and also it is highly favourable to design low cost efficient localization mechanism for (WSNs). This study presented an overview of localization techniques, different classification methods, reviewed important localization algorithm, and summarized their advantages and disadvantages for Wireless Sensor Networks and few possible future research directions